The Creation of Woman From a Dog’s Tail. A Folk Tale in Verse Among the Poems of Elżbieta Drużbacka - Piechura, Joanna (2019)
Elżbieta Drużbacka was one of the greatest court poets of the Late Baroque period in the Republic of Poland. She was reputed for her pastoral poems and a highly functionalised oeuvre, developed mainly in order serve the private interests of her patrons. The poem entitled O tym, jako kobieta z ogona psiego powstała (powieść biblijna przez Elżbietę Drużbacką) [Of the creation of Woman from a dog’s tail (a biblical tale by Elżbieta Drużbacka)], is wholly derived from a parabiblical etiological legend (ATU 798) – an unseemly source of inspiration for a poet of such stature. Since the poem belongs to a long tradition of popular Genesis narratives, oral and written, concerning the creation of Woman from different types of tails, the author suggests that in light of the text’s topic and style, Drużbacka’s 198 Joanna Piechura authorship remains uncertain. However, it is acknowledged that reading the poem with the poet’s biography as starting point offers a base of reference that allows for a comparative, cross-cultural analysis of Renaissance facetiae and picaresque satire in between literature, apocrypha and folklore. The author explains how differences in written and oral transmission may have influenced the shape of the poem in question as well as other versions of the tale, and demonstrates their cultural significance through discussing different parabiblical etiologies of judeochristian and folkloric descent.
Keywords: the Folk Bible; creation of Women; tail; facetiae